2016
DOI: 10.18047/poljo.22.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial modelling for describing spatial variability of soil physical properties in eastern Croatia

Abstract: Prostorno modeliranje radi opisivanja prostorne varijabilnosti fizikalnih svojstava tla u istočnoj Hrvatskoj Bogunović, I., Đekemati, I., Magdić, I., Vrbanić, M., Matošić, S., Mesić, M. Poljoprivreda

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Final suitability layer in form of thematic map is shown in Figure 3. Possible suitability values match standardization interval [1][2][3][4][5], with mean suitability value of 2.86 and standard deviation of 0.37. Suitability values range from 1.78 to 4.10, which indicates that no part of the study area fully satisfies the selected criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Final suitability layer in form of thematic map is shown in Figure 3. Possible suitability values match standardization interval [1][2][3][4][5], with mean suitability value of 2.86 and standard deviation of 0.37. Suitability values range from 1.78 to 4.10, which indicates that no part of the study area fully satisfies the selected criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Multicriteria analysis in agriculture is currently not developed as a recognizable procedure for calculation of land suitability in Croatia. However, variants of spatial modelling for suitability estimation in agriculture were used extensively in the eastern Croatia during the last decade (Vukadinović et al, 2011;Bogunović et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the capabilities that penetrometers have to spatially distinguish variations in mechanical properties in soils [ 20 ]. Soil resistance strongly depends on its volume, density, texture, structure and organic matter components [ 21 ]. It should be noted that for soil, settlement can change significantly in space depending on land use (fig.…”
Section: Effects Of Plowing Frequency On Soil Bearing Capacity and De...mentioning
confidence: 99%
“…In addition, Medeiros et al (2010) found a similarity between the results obtained using a manual penetrometer and those obtained with the electronic penetrometer when detecting the critical depth of compaction of three types of soil: silty, clayey and sandy. In all cases, penetrometer resistance strongly depends on the soil bulk density, texture, structure and soil organic matter content (Cassel, 1982;Bogunovic et al, 2016). It should also be noted that soil compaction can vary significantly in space depending on land use.…”
Section: Bulk Density Texture and Vertical Resistance Of Soilsmentioning
confidence: 99%
“…When these properties exceed critical values, plant growth is severely restricted (Medeiros et al 2010). Several factors influence soil compaction which may include different tillage tools, depth and speed of ploughing, moisture content, texture or soil cover residue (Bogunovic et al 2016). Experimental results studied variations of crop yield as a function of the level of subsidence of the surface horizons (Richard, 2008) but the influence of soil stress on the strength of agricultural equipment has been less studied.…”
Section: Introductionmentioning
confidence: 99%